Estudo da estabilidade global de um edifício em concreto armado para diferentes subestruturas de contraventamento - Lorenzetti, Caetano Alberto Del Carpio (2018)
This paper is focused on the study of the overall stability of a reinforced concrete building for three different bracing substructures: beam-pillar frames, wall-pillars and hard core. For this purpose, five examples were designed simulating those structural arrangements, in order to obtain information about the structure displacements, structural efforts and the amount of all the materials needed. Stability parameters – alpha parameter and gamma-z coefficient – were also calculated in order to evaluate the overall stability of the building and to estimate global second-round effects. Besides that, the paper brings forward a preliminary study of the software Alto QI Eberick, employed for the modelling, in a way to achieve a better understanding about how this computational program handles with structural dimensioning criteria and the variables that influence the analysis of the overall stability of buildings. It was concluded that the three proposed solutions for the building bracing system presented the expected results regarding the overall stability of the building. The system with wall-pillars greatly increased the rigidity of the system when compared to that based on beam-pillar frames, expressively reducing the axial compressive stresses in the other pillars. Meanwhile, due to its high rigidity, the presence of the rigid core allowed a greater reduction of the other elements, making the structure less costly.